2018
DOI: 10.22502/jlmc.v6i2.228
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pre-hospital delay before reperfusion therapy in patients with ST-segment elevation myocardial infarction

Abstract: Introduction: Cardiovascular disease remains the main cause of death in the world, and myocardial infarction represents the main contributor to this mortality. Timely restoration of myocardial blood flow with reperfusion therapy is crucial. Pre-hospital delay is a major obstacle for early reperfusion therapy and has negative impact on mortality and left ventricle function. Methods: A prospective study was carried in cardiology unit of a medical college from August 2013 to December 2017. Cases of acute ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Cardiac cause for admission was in 71.3%. Cardiac causes for readmission were also quoted as 42% by Shah et al 9 ,57.8% Atti et al 10 20 As prehosptial time 21 and door to needle time 22 and door to balloon time 33 is longer in our settings, revascularization cannot be done in time and significant improvement in both ejection fraction and wall motion abnormalities does not occur even after treatment. Anemia, defined according to WHO in male with haemoglobin < 13gm/dl and female <12 gm/dl, was in 83 (58%) patients which was similar to other study.…”
Section: Introductionmentioning
confidence: 52%
“…Cardiac cause for admission was in 71.3%. Cardiac causes for readmission were also quoted as 42% by Shah et al 9 ,57.8% Atti et al 10 20 As prehosptial time 21 and door to needle time 22 and door to balloon time 33 is longer in our settings, revascularization cannot be done in time and significant improvement in both ejection fraction and wall motion abnormalities does not occur even after treatment. Anemia, defined according to WHO in male with haemoglobin < 13gm/dl and female <12 gm/dl, was in 83 (58%) patients which was similar to other study.…”
Section: Introductionmentioning
confidence: 52%
“…8 , 9 , 10 , 27 , 28 , 29 Few studies have reported a higher delay among women, 14 , 28 but many studies including ours did not find so. 27 , 28 , 30 , 31 The primary reason for delay identified in all studies has been the lack of awareness of the symptoms to be related to MI or stroke resulting in non-recognition of the severity of their illness. Our study confirms these findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult for them to understand every minute of delay in treatment of patients with STEMI can affect 1-year mortality, both in thrombolytic therapy and primary angioplasty and the risk of 1-year mortality can be increased by 7.5% for each 30-minute delay. 15,16,17 Once the patient in the periphery became stable and chest pain free, many refused to complete doses of medicine and request for early discharge. Mean hospital stay was for 3.1±1.1 days.…”
Section: Discussionmentioning
confidence: 99%